Après Nebrija, Villalón Des premiers grammairiens des langues romanes - Mencé-Caster, Corinne (Studies, 2021)
Villalón wrote one of the first complete grammars of Castilian in 1558. He contributed to the description and codification of Castilian, as well as to the invention of a metalanguage specific to Castilian. The present study retraces in six chapters the sinuous trajectory of the first grammarians of the Romance languages, focusing on Villalón's grammar and linking it to that of Nebrija. It aims to shed light on the modalities of standardisation and metalinguistic description of Castilian, based on the notions of linguistic awareness, norm, sentence, article and completeness.